INTEGRASI NILAI-NILAI KECERDASAN EMOSIONAL DALAM KURIKULUM PENDIDIKAN AGAMA ISLAM DI SMA: PERSPEKTIF DANIEL GOLEMAN - Riyadi, Ivan (State Institute of Islamic Studies (IAIN) Palu, 2015)
This articel was conducted based on the consideration that the current emotional intelligence is still indispensable in shaping the behavior of students. With specification on the subjects of Islamic education, this article tried to connect the emotional intelligence of high school students on Islamic Education. This article examines to determine how Islamic religious education policies that have been implemented in high school and to determine the relevance of emotional intelligence of high school students against the teachings of Islam. To get a complete this article. libarary research approach.Â Data was collected through literature study includes studying, studying and citing theories or concepts from a number of literature. Books, journals, magazines and others. It can be applied to educate children who are emotionally intelligent with the ability to recognize self-managing emotions productively utilize emotions, empathy, and the ability to build social relationships.